2012
DOI: 10.1021/jf303440j
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Chlorogenic Acid on Nitric Oxide Status, Endothelial Function, and Blood Pressure in Healthy Volunteers: A Randomized Trial

Abstract: There is mounting evidence that specific dietary polyphenols can enhance vascular health by augmenting nitric oxide. Our aim was to investigate the acute effects of chlorogenic acid, an important dietary phenolic acid present in coffee (400 mg, equivalent to 2 cups of coffee), on nitric oxide status, endothelial function, and blood pressure. Healthy men and women (n = 23) were recruited to a randomized, double-blind, placebo-controlled, crossover trial. Chlorogenic acid resulted in significantly higher plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 41 publications
4
82
1
2
Order By: Relevance
“…In our study, coffee consumption led to a significant decrease of systolic blood pressure in the D-group, but final values reached were not significantly different from the group consuming M-coffee. Dark roast coffee has been reported previously to increase rather than reduce blood pressure, which is thought to result from a lower content of CQA and a higher content of hydroxyhydroquinone, when compared to mildly roasted or green coffee [14,42,43]. The reason for the difference in outcome is not known, since NMP concentration had not been measured in above studies, and the content of hydroxyhydroquinone was not determined in the coffee preparations used in our study.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, coffee consumption led to a significant decrease of systolic blood pressure in the D-group, but final values reached were not significantly different from the group consuming M-coffee. Dark roast coffee has been reported previously to increase rather than reduce blood pressure, which is thought to result from a lower content of CQA and a higher content of hydroxyhydroquinone, when compared to mildly roasted or green coffee [14,42,43]. The reason for the difference in outcome is not known, since NMP concentration had not been measured in above studies, and the content of hydroxyhydroquinone was not determined in the coffee preparations used in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, hippuric, vanillic, and homovanillic acids have structural homologies to the pharmacologic NADPH oxidase inhibitor apocynin (61) and have been proposed as potent NAPDH oxidase inhibitors in endothelial cells (31), with ferulic acid capable of restoring endothelium dependent vasodilation of aortas from spontaneously hypertensive rats via a reduction in NADPHdependent superoxide production in aortas (62). Furthermore, the ingestion of chlorogenic acid has also been shown to improve endothelium-dependent vasodilation and decrease blood pressure in spontaneously hypertensive rats via decreased NADPHdependent superoxide anion production and a parallel increase in urinary nitric oxide metabolites (63), whereas pure chlorogenic acid has decreased blood pressure in healthy volunteers (64). Our data suggested that circulating small phenolic metabolites that derive from the ingestion of anthocyanins and other flavonoids/ polyphenols present in blueberry may inhibit NADPH oxidase and, thus, lead to increased nitric oxide bioavailability and subsequent increases in endothelial-dependent dilation.…”
Section: Discussionmentioning
confidence: 99%
“…There is outstanding potential for the use of CGA and its derivatives and metabolites in the treatment of several inflammation and oxidative stress-related pathological situations. There has been a wide range of dosage for systemic administration of CGA, from 2.5 to 400 mg/kg (Hunyadi et al 2012;Karthikesan et al 2010a, b;Mubarak et al 2012;Yun et al 2012). However, systemic CGA treatment has antiinflammatory, analgesic, and flap-healing properties in vivo when used in the same dosage as in our study (Dos Santos et al 2006;Bagdas et al 2013Bagdas et al , 2014.…”
Section: Discussionmentioning
confidence: 99%